PROSPEK MASA DEPAN BAHAN MEMBRAN UNTUK TERAPI REGENERATIF PERIODONTAL: TINJAUAN PUSTAKA - Dian Eka Satya; Sri Oktawati (B-Dent: Jurnal Kedokteran Gigi Universitas Baiturrahmah, 2021)
Introduction: Periodontal regenerative therapy goals are to prevent and repair the soft and hard tissue that has been damaged by the infection. The membrane has been used as a material of soft tissue periodontal regenerative therapy. Resorbable and non-resorbable membranes were used as physical barriers to avoiding the growth of connective and epithelial tissue into the defect area. This review will be discussed about the new development of membrane materials for Guided Tissue Regeneration (GTR) which is used in regenerative periodontal therapy along with the advantages of each biomaterial. Review: The barrier membranes used for GTR can be divided into three generations. The first-generation membrane has many structural, mechanical, and biofunctional limitations. The second and third generation of membrane materials is still being developed. The third generation is claimed to function not only as a barrier but also as an antimicrobial agent. It also enhances tissue adhesion and releases the growth factors which are needed for periodontal regeneration. The development of materials used in GTR therapy has been upgraded from only as a barrier to the perspective from being only a barrier to a delivery agent such as antibiotics, growth factors, adhesion factors in the third generation. Conclusion: The GTR procedure has long been used in periodontal regenerative therapy. The latest development for GTR materials not only works as a barrier but also has both bioactive and multilayered nanofibrous membranes that are potential for use in periodontal tissue engineering.